2021
DOI: 10.1007/s10389-020-01455-0
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic: an online-based survey of knowledge, perception, and adherence to preventive measures among educated Nigerian adults

Abstract: Aims One of the ways to manage the current coronavirus disease 2019 (COVID-19) pandemic is to monitor the public knowledge, risk perceptions, adherence to preventive measures, and level of preparedness behaviors. This is important in resourcelimited countries. This study determined the knowledge and perception regarding COVID-19; adherence to COVID-19 preventive measures; as well as predictors of self-perceived risk of contracting COVID-19 among Nigerian adults. Methods A cross-sectional study was conducted am… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…A major source of information utilized among respondents in this study is the internet, healthcare professions (Doctors, Health, and Pharmacist), and social media platforms. This finding collaborates Oyeyemi et al (2020) study that reported internet as the most common source of information about COVID-19 also in a similar study understudied in Egypt by Abdelhafez et al (2020) the use of internet was reported to be highly used. Likewise, Olaimat et al (2020) in their study on knowledge and information sources about COVID 19 among University students in Jordan reaffirm that the most common source of the student's information about COVID 19 was the internet which includes, electronic news websites and social media such as twitter, Facebook, YouTube, Instagram, Snapchat and WhatsApp.…”
Section: Testing Of Hypothesessupporting
confidence: 89%
“…A major source of information utilized among respondents in this study is the internet, healthcare professions (Doctors, Health, and Pharmacist), and social media platforms. This finding collaborates Oyeyemi et al (2020) study that reported internet as the most common source of information about COVID-19 also in a similar study understudied in Egypt by Abdelhafez et al (2020) the use of internet was reported to be highly used. Likewise, Olaimat et al (2020) in their study on knowledge and information sources about COVID 19 among University students in Jordan reaffirm that the most common source of the student's information about COVID 19 was the internet which includes, electronic news websites and social media such as twitter, Facebook, YouTube, Instagram, Snapchat and WhatsApp.…”
Section: Testing Of Hypothesessupporting
confidence: 89%
“…For instance, Carlucci et al [29] concluded that women, most educated people, middle-aged individuals, and health workers are more likely to adhere to lockdowns and other imposed policies. Jabbari et al [30] and Oyeyemi et al [31] reached similar conclusions, indicating that people's education (health literacy) plays a vital role in containing outbreaks. Furthermore, the success of hospitals largely depends on the complexity of cases handled therein [32].…”
Section: Literature Reviewmentioning
confidence: 74%
“…recorded low adherence(Bante et al 2021;Abeya et al 2021;Ditekemena et al 2021). In Nigeria, the level of adherence was mixed, with high adherence observed in some places and low in others (Nnama-Okechukwu, Chukwu and Nkechukwu 2020;Bolarinwa et al 2020;Adesegun et al 2020;Ejeh et al 2020;Oyeyemi et al 2021). Some studies established a connection between Covid-19 information sources and adherence to the prescribed preventive measures.…”
mentioning
confidence: 99%